Implementation of Human Resource Management in Enhancing Competitive Advantage : (A Multi-Case Study at MAN 2 Kediri City and MAU MBI Amanatul Ummah Pacet Mojokerto) - Romadlon Romadlon; Ahmad Tanzeh; Ngainun Naim (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study explores the implementation of human resource development management as a strategic effort to enhance task performance in educational institutions. The research was conducted at MAN 2 Kediri City and MAU MBI Amanatul Ummah Pacet Mojokerto, where notable improvements in information and technology mastery were observed. These improvements stemmed from various capacity-building activities, including computer proficiency training, computer-based learning workshops, excellent service training, teacher participation in science olympiad competitions, and other quality enhancement programs. Employing a qualitative approach, data were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted using individual site analysis and cross-site comparison, while data validity was ensured through credibility, transferability, dependability, and confirmability criteria. The findings reveal that to strengthen competitive advantage in madrasahs, school leaders undertake comprehensive human resource management practices. These include needs analysis through vacant position mapping and recruitment planning, teaching hour allocation, job analysis, and structured recruitment processes involving written tests, microteaching, and interviews. Furthermore, human resource development is carried out through adherence to Standard Operating Procedures (SOP) and continuous professional training for educators. The study concludes that strategic human resource development contributes significantly to institutional competitiveness and educational quality. It recommends sustained investment in teacher capacity building and structured HR planning to support long-term performance improvement.